CO-Releasing, Antioxidant, Antibacterial, Zeta Potential, Theoretical, and Electrochemical Analysis of [Mn(CO)3(bpy)L]OTf Type Complexes - Ustun, Elvan; Sakar, Dolunay; Ayvaz, Melek Col; Celebi, Mutlu Sonmez; Erturk, Omer (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
In pharmaceutical chemistry, both N-heterocyclic compounds and metal carbonyl complexes are well-known families because their several bioactivities. N-heterocyclics have been used biomedical and agricultural applications while carbonyl complexes have been utilized for labelling biomolecules and releasing carbon monoxide. Thus, the metal carbonyl derivatives with N-heterocyclic ligands have been researched. In this study [Mn (CO)3(bpy)(1-phenylimidazole)]OTf and [Mn(CO)3(bpy)(1-(4-chlorophenyl)imidazole)]OTf [bpy:2,2 '-bipyridiyl, OTf:SO3CF3) complexes were synthesized and characterized. CO-releasing properties, antioxidant and antibacterial activities of these complexes were analyzed, and the bioactivity results were compared with DFT/TDFFT and molecular docking methods. Additionally, the stability and activity of the molecules were investigated via zetasizer and UV/VIS Spectroscopy.
Keywords: N-heterocyclic; Manganese complexes; CO-releasing; Antioxidant; Antibacterial; METAL-CARBONYL-COMPLEXES; MANGANESE(I) TRICARBONYL COMPLEXES; DESIGN; ANTICANCER; MOLECULES; DERIVATIVES; INHIBITORS; REACTIVITY; LIGANDS; AGENTS; Chemistry; Crystallography